Simple Phenazine‐Based Compounds Realizing Superior Multicolored Emission. Issue 6 (10th February 2022) - Xie, Mingchen; Cai, Jiaheng; Wang, Xueqi; Shan, Tong; Jung, Sinyeong; Zhong, Hongliang; Guo, Xiaojun; Zhou, Dongying; Li, Tao
Abstract: A new family of phenazine‐based compounds is synthesized to achieve multicolored emission from deep blue (418 nm) to red (625 nm). Emitters have unique hybrid local and charge‐transfer excited states for S1, T1, T2, and even higher‐layer excited states, respectively, while all emitters possess thermally activated delayed fluorescence (TADF) nature. The rigid structure of phenazine and steric hindrance of donors are sufficiently utilized to suppress the nonradiative consumption, manipulate the configurations of excited states, and regulate the luminescence color. Organic light‐emitting diodes exhibit superior multicolored emission with 10.74% external quantum efficiency. Employing such kind of simple‐structured and easily synthesized compounds to realize multicolored emission would provide a new strategy for designing high‐performance and multicolored TADF materials. Abstract : The phenazine group is utilized for the first time to synthesize multicolored thermally activated delayed fluorescence molecules for realizing the emission from deep blue to red. They feature unique hybrid local and charge‐transfer‐type excited states, ultrahigh exciton utilization efficiencies, and 10.74% maximum external quantum efficiency. These superior performances make them promising candidates for organic light‐emitting diodes.